Adjusting Fiscal Balances for Asset Price Cycles - Price, Robert (OECD Economics Department Working Papers, 2011)
This paper develops a method for adjusting structural budget balances for asset price cycles and presents estimates of structural budget balances corrected for house-price and equity-price cycles for OECD countries. The traditional cyclically adjusted budget balance indicator, which is the basis for measuring structural or underlying budget balances, does not adjust for the effects of cyclical fluctuations in asset prices. This implies that, by default, asset price related effects on revenues are included in the structural budget measure. That can be misleading for policy makers where asset price shifts prove to be temporary, leading to pro-cyclical fiscal action, especially where policy makers cut tax rates or increase spending in response to unexpected revenue buoyancy. The paper first presents econometric estimates of tax revenue elasticities measuring the response of the major tax categories to house-price and equity-price movements. It then uses these elasticities to adjust revenues for the effects of asset price cycles measured in terms of deviations from "fundamental" and smoothed asset prices. To the extent that asset price movements are independent of, and uncorrelated with, the output cycle, the adjustment can be added to the conventional structural balance to create an asset-adjusted structural balance. The analysis is retrospective, but an important consideration has been to improve the identification of cyclical revenue fluctuations as they occur, or as they are incorporated into fiscal projections, and to be able to recognise the source of revenue "surprises"